Business Plan Motorcycle Workshop for Tuning and Performances - KADERI, ZULAIHA; Ahmad, Abd Razak (Research in Management of Technology and Business, 2023)
Abstract: This business plan is to provide the guidelines for Mr. Rizal (owner) in term of business administration, financial projection and sales and marketing activities for the business venturing in motorcycle workshop specialize for engine tuning and performance. Common motorcycle workshop focusing on repair and service job only, however, these services not really give full satisfaction for the customer in term of motor speed, engine health and achieving optimum performances of their motorcycle. The growth of motorcycle sales unit in Malaysia gives significant demand on aftermarket application services such as maintenance, repairing, dynojet and engine tuning for motorcycle. The business emphasis to be service provider on rapidly growing demand for speed and performances. The company will have 3 key business segment which help to serve the needs and distinguished itself from the competition which are: dynometer test and ECU tuning, motorcycle repairing and maintenance service, spare parts and accessories selling with installation. Digital lifestyle nowadays set a mould of social media as the powerful marketing tools. The 9 block elements of Business Model canvas (BMC) will help the company to clearly define and communicate the overall business concept. With the start-up capital of RM 78,650.00 from the owner pensioner fund, the company wants to successfully venture in business in aftermarket application industry.